The Influences OF Intrinsic Motivation, Training, and Work Engagement on Employee Performance in DKI Jakarta - Adeline Anugrah Raphani (Universitas Mercu Buana, 2021)
The purpose of this research is to examine the influence of Intrinsic Motivation, Training, and Work Engagement toward Employee Performance for employees in DKI Jakarta. 107 respondents were collected as the research sample using Slovin’s formula with 10% error tolerance and purposive sampling method. The data is analyzed using Structural Equation Modeling approach. The research findings indicate that Intrinsic Motivation has positive and significant relationship toward Employee Performance. On the other hand, Training and Work Engagement have negative and insignificant relationship toward Employee Performance.